STRATEGY OF ENTERPRISE MANAGEMENT UNDER MARTIAL LAW - ULIANCHENKO, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The aim of this article is to provide a comprehensive analysis and scientific substantiation of modern approaches to the formation of an effective enterprise management strategy under martial law. This research is conducted in the context of drastic transformations in the external environment, characterized by heightened uncertainty, disruption of logistical and production processes, and significant threats to the safety of personnel and material-technical resources. The study pays particular attention to identifying viable mechanisms for adapting managerial decisions to crisis conditions, ensuring business continuity and resilience, preserving human capital, and defining strategic priorities focused on enterprise recovery and long-term sustainable development in the post-crisis period.The article synthesizes current theoretical and practical approaches to strategic enterprise management during wartime. It examines the multifaceted impact of military actions on key functional components of the management process, including planning, organization, motivation, and control. The research highlights major challenges and risks that business leaders encounter in volatile and crisis-driven environments. A special focus is placed on the application of adaptive management models that promote organizational flexibility, enable rapid response to dynamic changes in the external context, and safeguard the stability of business operations under extreme conditions.In addition, the study summarizes the practical experience of Ukrainian enterprises that have successfully implemented anti-crisis strategies. These include diversification of supply chains, relocation of production facilities, integration of digital technologies into operational processes, and strengthening of corporate social responsibility initiatives aimed at supporting employees and local communities. Drawing on this empirical analysis, the article proposes a set of strategic directions and policy recommendations to enhance enterprise management efficiency both during martial law and in the post-war recovery phase. These findings contribute to the development of resilient and future-ready business models capable of withstanding severe external shocks.
Keywords: strategic management; enterprise; martial law; crisis management; business adaptation; risks; organizational resilience; managerial decisions; transformation; crisis conditions